KEBIJAKAN PERIZINAN DALAM PEMBANGUNAN KUDUS EXTENSION MALL (KEM) HYPERMART DAN GEJOLAK SOSIAL MASYARAKAT KABUPATEN KUDUS - Rusmila Tafani (Journal of Politic and Government Studies, 2013)
KEBIJAKAN PERIZINAN DALAM PEMBANGUNANKUDUS EXTENSION MALL (KEM) HYPERMART DANGEJOLAK SOSIAL MASYARAKAT KABUPATEN KUDUSRUSMILA TAFANID2B009002(milla.tafani@yahoo.com)ABSTRACTThis study aimed to investigate the reasons and considerations of Kudus LocalGovernment that permits the construction of KEM Hypermart in despite oppositionfrom the community. There are three main things to be considered by the Kudus LocalGovernment related to the licensing for KEM Hypermart construction. Normatively, PT.Mulia Persada Pertiwi has completed the requirements and the procedures for applyingfor licenses KEM Hypermart establishment in accordance with the applicable rules. Inaddition to increasing the local revenue, KEM Hypermart with upscale market segmentbeing economic consideration of the Kudus Local Government. Management KudusMonument as a cultural icon is the responsibility of PT. Mulia Persada Pertiwi alsofavorable for the local government in terms of economic and social development.